Optimizing Data Flow: A Unified Approach for Product, Pricing, and Revenue Sync in Enterprise Systems (International Journal of Engineering & Extended Technologies Research (IJEETR), 2024)
This study proposes an integrated strategy towards maximizing the flow of data within enterprise systems by harmonizing product, pricing and revenue synchronization. The suggested model takes advantage of MuleSoft-based integration to simplify the process of data interchange between ERP and CRM and financial platforms. The architecture standardises the communication of key data aspect by embracing canonical data models and transformation orchestration, which guarantees a smooth communication among disparate systems. Other features that are included in the framework are centralized governance frameworks and error management, which strengthens the integrity of data, financial integrity, and transparency of operations. With a single data synchronization system, silos are removed, less manual intervention is made, and fewer errors are minimized, all of which lead to more efficient and accurate decision-making. Moreover, MuleSoft APIs integration promotes scalability and flexibility, and organizations can easily incorporate the changes in the business needs. The research shows that the proposed architecture does not only help to streamline the data flow between different systems of an enterprise, but also to promote the performance of the whole organization in terms of improved product, pricing, and revenue management. The study offers a worthy paradigm to businesses that want to maximize their data synchronization activities to achieve real-time, correct information and enhanced functionality throughout all their networks.
Keywords: MuleSoft; Data Synchronization; Product and Pricing Integration; Revenue Data Management; API Architecture; Enterprise Systems